Beli atau Tidak? Keputusan Konsumen Anomali Café Berdasarkan Pertimbangan Harga dan Brand Image - In May Sari; Abdul Gofur (Fakultas Ekonomi dan Bisnis Universitas Nasional, 2022)
The purpose The level of competition for coffee shops is increasing, therefore this study aims to determine whether price and brand image are the determining factors for Anomali Cafe consumers in deciding whether to buy or not the coffee outlet product. Methodology The population of this study is limited to consumers of Anomali Cafe Setiabudi outlets, South Jakarta. Samples were taken from the population by accidental sampling, namely anyone who coincidentally met with the researcher until the sample reached 90 respondents. This measure is according to the rules of experts based on the adequacy of the sample for social research. The proposed hypothesis testing was analyzed based on statistical techniques, namely by multiple linear regression analysis. Findings Price and brand image are strong factors in determining consumer buying decisions. Suggestion Pricing at coffee outlets must be continuously monitored and adjusted to suit consumer perceptions because price is a strong determining factor in consumer purchasing decisions.